Gluten-Free Diet: Always as Easy, Useful, and Healthy as People Think? - Flores Quan, Cinthia V.; Redecillas Ferreiro, Susana E.; Segarra Cantón, Oscar (Journal of Child Science, 2018)
A diet free of wheat and other gluten-containing foods is followed by individuals with celiac disease and by unaffected persons. Although the evidence and pathophysiology of gluten-induced symptoms are well established in celiac disease, they are still limited in non-celiac patients. At present, a gluten-free diet is often seen as a healthy lifestyle change instead of an adequate dietary therapy required for a specific condition. Consequently, the market for gluten-free products is steadily growing and improving; in fact, pseudocereals and genetically modified foods and crops are gaining importance in attempts to cover the dietary and nutritional needs of a population that demands it. There is currently interest not only in modifying crops to improve their agronomic traits and product flavor and appearance, but also to improve the nutritional content of crops and/or to silence certain genes with greater risk of allergenicity. However, the gluten-free diet trend is not hazard free, and many people can end up struggling with dietary disorders after making this decision. Therefore, we should be familiar with and take into account the potential shortage of certain nutrients in some of the gluten-free alternative products, which are now being fortified to prevent nutrient deficiencies and their consequences.
Keywords: gluten; pseudocereals; celiac disease; gluten-free diet